Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.commatsci.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of hydrogen functionalized graphene allotropes

Abstract: Molecular dynamics (MD) simulations have been performed to investigate the mechanical properties of hydrogen functionalized graphene allotropes (GAs) for H-coverage spanning the entire range (0-100%). Four allotropes (graphyne, cyclic graphene, octagonal graphene, and biphenylene) with larger unit lattice size than graphene are considered. The effect of the degree of functionalization and molecular structure on the Young's modulus and strength are investigated, and the failure processes of some new GAs are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…It can also directly modify the interaction of graphdiyne with the environment, which can be exploited in several technological applications [21,22]. Because of these properties, a considerable number of papers on pristine and functionalized graphynes and graphdiynes has been recently reported [16,[23][24][25][26][27]. These results illustrate the remarkable variation in mechanical properties, fracture patterns, and exciting exotic electronic and geometrical properties exhibited by some hydrogenated graphyne and/or graphdiynes structures.…”
Section: ! 3!mentioning
confidence: 85%
“…It can also directly modify the interaction of graphdiyne with the environment, which can be exploited in several technological applications [21,22]. Because of these properties, a considerable number of papers on pristine and functionalized graphynes and graphdiynes has been recently reported [16,[23][24][25][26][27]. These results illustrate the remarkable variation in mechanical properties, fracture patterns, and exciting exotic electronic and geometrical properties exhibited by some hydrogenated graphyne and/or graphdiynes structures.…”
Section: ! 3!mentioning
confidence: 85%
“…In summary, we have shown that multi-layer stacks of continuous graphene membrane could provide a revolutionary advance in ballistic barriers. In fact, graphene is only one example of the broad field of two-dimensional polymers [36][37][38][39][40][41][42][43][44], many of which would be expected to exhibit nominally isotropic high strength and stiffness. Other two-dimensional materials such as BN [45] and MoS 2 [46] are also predicted to provide excellent in-plane mechanical properties although at values that are somewhat lower than graphene.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen functionalization significantly lowers the tensile strength of graphene allotropes [17]; shear strength of graphene also reduces with increasing hydrogen adatom concentration [18]. Adsorption of methyl functional groups onto graphene greatly reduces its tensile strength, especially when methyl groups are arranged in lines perpendicular to the tensile direction [30].…”
Section: Modeling Of Graphenementioning
confidence: 99%
“…The adsorption of adatoms could have a significant impact on the non-bonded interactions between graphene and composite matrix. Molecular dynamics simulation studies reveal that hydrogen adsorption can have a significant impact on the strength of graphene and its allotropes [17,18]. On the other hand, dangling bonds in defective graphene, which are created by defects (e.g.…”
Section: Introductionmentioning
confidence: 99%